The use of augmented reality for solving arithmetic problems for preschool children - Zhou, Siyuan; Sun, Xu; Shi, Zhiyu; Lu, Yanyi (2020)
Preschool children are required to acquire problem-solving ability and related time and sequence concepts to solve mathematical story problems. The maturation and pervasion of disruptive technologies, such as augmented reality (AR), may help preschool children to better acquire this knowledge and skills. However, it is still unknown how preschoolers would make use of AR as a learning tool for tackling arithmetic story problems with the involvement of the concepts of time and sequence. Consequently, the present study attempted to employ direct observation and interview methods to compare and gain insights into young children’s learning behaviors under traditional 2D pictorial and AR contexts. In line with the early development trajectories of a normal child aged 4–6 years old, a series of planned arithmetic problems which primarily comprised seriation (e.g. first, second, third) and scheduling (e.g. arriving, leaving) concepts were structured in scenario-based stories and designed specifically for preschool children. The findings of the current study reveal that AR intervention may well develop the problem-solving and independent mathematical thinking ability for preschool children by encouraging them to consider all information involved in the story problems, rather than simply guessing the answer from a 2D pictorial mode. Finally, based on the fact that the majority of preschool children still rely on a concrete counting method, the recommendation is to integrate AR technology into the traditional pictorial scenarios for the purpose of supporting the development of children’s ability to solve arithmetic story problems